Privatisation and Financial Performance in Egypt Since 1991 - Abdeldayem, Marwan Mohamed; Dulaimi, Saeed Hameed AL (Asian Economic and Financial Review, 2019)
This study aims to empirically examine the financial and operating performance of Egyptian privatised companies. The study compares the pre- and post-privatisation financial and operating performance of 60 companies from Egypt that have experienced privatisation through different methods during the period from 1991 and 1997. There were significant increases in the mean and median levels of profitability, operating efficiency, capital investment, output and dividends for the whole sample of companies after privatisation. There were significant decreases in the mean and median of both leverage ratios and employment levels. Further analysis was also undertaken using the three different background characteristics (i.e. size of company, type of industry and privatisation methods). No significant differences were detected in the Kruskal Wallis test analysis of privatisation methods. The Wilcoxon test, the Proportion test and the Kruskal Wallis test analyses for the company size and industry type revealed some significant results. Overall, the findings do seem to support the broad benefits of the Egyptian privatisation programme and the improvements in the financial and operating performance of the privatised companies.